Soziologie - sociology in the German-Speaking World - Hollstein, Betina; Greshoff, Rainer; Schimank, Uwe; Weiß, Anja (Soziologische Revue, 2021)
Frontmatter -- Contents -- A Companion to German-Language Sociology -- Culture -- Demography and Aging -- Economic Sociology -- Education and Socialization -- Environment -- Europe -- Family and Intimate Relationships -- (Felt) Body. Sports, Medicine, and Media -- Gender -- Globalization and Transnationalization -- Global South -- History of Sociology -- Life Course -- Media and Communication -- Microsociology -- Migration -- Mixed-Methods and Multimethod Research -- Organization -- Political Sociology -- Qualitative Methods -- Quantitative Methods -- Religion -- Science and Higher Education -- Social Inequalities-Empirical Focus -- Social Inequalities-Theoretical Focus -- Social Movements -- Social Networks -- Social Policy -- Social Problems -- Social Theory -- Society -- Space. Urban, Rural, Territorial -- Technology and Innovation -- Work and Labor -- List of Contributors -- Index